As dinâmicas urbanas territoriais e as relações de exclusão social nos bairros Maméd e Alfredo de Castro na Cidade de Rondonópolis, Mato Grosso - Medeiros, Reuber Teles (2016)
This work aimed to identify the urban structure and territorial dynamics in two areas of the outskirts of Rondonópolis, Vila Mamed and Alfredo de Castro neighborhood, characterizing the socioeconomic conditions and the specific aspects in which these two communities experience their daily lives. Within this context, different realities can be identified in both places, as a consequence of several factors, such as the realities that exist, the time of foundation of the neighborhoods and the endowment of infrastructures, since Vila Mamed is an old and, The neighborhood Alfredo de Castro is recent, still not having land regularization. With the field research done in the neighborhoods with a sample of the community, it was sought to discover the conditions by which these residents survive, their needs in the social sphere and, especially, in what concerns the part of infrastructure existing in the neighborhood, in the sense of Identify existing shortcomings and also outline proposals for public policies regarding urban planning, in a way that will resolve the possible environmental and social impacts verified in the reality of the neighborhoods. It was also identified the demands of infrastructure and the need to implement public policies, such as, for example, improvement in the urban structure, where in the Alfredo de Castro neighborhood was predominant the lack of street paving, with 19 people, corresponding to 40, 4%. In Vila Mamed the predominant issue was the absence of street signs, with 32 responses, which corresponds to 59.2%. Another situation that needs improvement is in the aspect of public security, because it is an unsafe neighborhood, according to some residents interviewed. Finally, this research represents a contribution to urban planning and management, since it recognizes a territorial configuration differentiated from the opinions of the communities involved, identifying numerous needs and possibilities of intervention in peripheral areas, in search of better living conditions in a collective perspective.